How does physical exercise with health purposes or recreational sports affect the left atrium? Meta-analysis of observational and experimental studies. - Florio, Lucia; Rivoir, Santiago (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Introduction: Physical exercise affects the morphology and function of the left atrium. Elite athletes have increased volume without increasing stiffness. The effect of exercise on the atria of the general population is less well known. Objective: To evaluate the effect of aerobic exercise on the anatomy and function of the left atrium. Main objective: compare left atrial volume indexed to body surface area; secondaries: to compare ejection fraction and left atrial peak longitudinal strain, E/e´ ratio and new atrial fibrillation in a population that practices aerobic exercise for at least 4 weeks vs non-active. Method: Meta-analysis of observational or experimental studies. Excluded: subjects with baseline atrial fibrillation, non-aerobic exercise; elite/professional athletes. Keywords: “physical exercise AND left atrial function”, until 2/21/2022 in Pubmed, Scielo, clinicaltrials.gov and hand-search. Results: Eleven studies included in main outcome; 789 subjects, median age 52 years; female sex 24%. Main outcome (only statistically significant): left atrial index volume 2.65 ml/m2 ˃ in the exercise group (p=0.006). No results were found for incidence of atrial fibrillation. Conclusions: In the general population, aerobic exercise favors dilation of the left atrium. The relevance is doubtful due to contradictory and non-significant results on atrial stiffness.